"My Profession Chose Me:" Precarity, Pragmatism, and Professionalism in Caribbean and West African Immigrant Domestic Workers' Narratives. Issue 1 (May 2017) - Glaser, Lee
Abstract: Extensive literature on care work or domestic work — childcare, eldercare, and housecleaning — in the United States and internationally has highlighted how the sector's affective aspects, e.g., intimacy, personalism, and fictive kin relationships, extract "surplus emotional labor" (Hochschild 1983 from women workers, who, in turn, often justify their caregiving labor through expressions of sentiment and kin obligation. In this article, I draw on three women's narrative framings of their domestic work jobs to argue that immigrant women in New York City emphasize structural, practical, and contextual elements of their domestic/caregiving labor, challenging constructions of care sector labor as evidence of innate caring aptitudes, womanly duty, or moral service. These characterizations have direct labor policy implications for paid care work — as evidenced in recent reforms. They also provide a theoretical basis for broader redistributive politics linking paid and unpaid caregiving labor.